2017
DOI: 10.3906/elk-1602-113
|View full text |Cite
|
Sign up to set email alerts
|

Smart frequent itemsets mining algorithm based on FP-tree and DIFFset data structures

Abstract: Association rule data mining is an important technique for finding important relationships in large datasets.Several frequent itemsets mining techniques have been proposed using a prefix-tree structure, FP-tree, a compressed data structure for database representation. The DIFFset data structure has also been shown to significantly reduce the run time and memory utilization of some data mining algorithms. Experimental results have demonstrated the efficiency of the two data structures in frequent itemsets minin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The negFIN algorithm (Aryabarzan et al, 2018) adopts the bitwise operation to extract the NegNodesets structure of the itemset and uses a set enumeration tree to generate frequent itemsets, which is pruned by the promotion method. FDM is a new algorithm based on FP-tree and DIFFset (Gatuha & Jiang, 2017) data structures, which can mine long and short patterns from dense and sparse datasets. The SS-FIM algorithm (Djenouri et al, 2017) performs a single scan of the transactional database to extract frequent itemsets, and the algorithm is less sensitive to the changes in the minimum support threshold set by the user.…”
Section: Related Workmentioning
confidence: 99%
“…The negFIN algorithm (Aryabarzan et al, 2018) adopts the bitwise operation to extract the NegNodesets structure of the itemset and uses a set enumeration tree to generate frequent itemsets, which is pruned by the promotion method. FDM is a new algorithm based on FP-tree and DIFFset (Gatuha & Jiang, 2017) data structures, which can mine long and short patterns from dense and sparse datasets. The SS-FIM algorithm (Djenouri et al, 2017) performs a single scan of the transactional database to extract frequent itemsets, and the algorithm is less sensitive to the changes in the minimum support threshold set by the user.…”
Section: Related Workmentioning
confidence: 99%
“…In the FP tree establishment step, [35] the database is scanned to identify the highfrequency itemsets that meet the minimum degree of support, and they are arranged according to the support degree, as shown in Table 3. After the database is scanned, the support degree of each itemset is compared with the minimum support degree, and the itemset with an insufficient threshold value is be deleted, as shown in Table 4.…”
Section: The Formula Is As Follows: Confidence (A⇒b) = P(a∩b)/p(a)mentioning
confidence: 99%
“…Many previous works [10], [26], [27], [28], [29], [30], [31], [33], [34], [35] have shown that pattern growth approaches based on prefix trees are more efficient than candidate generation-and-test approaches. However, pattern growth approaches are confronted with a problem that they have to spend much time in constructing many (conditional) prefix trees.…”
Section: A Motivationmentioning
confidence: 99%